1994
DOI: 10.1007/bf01231770
|View full text |Cite
|
Sign up to set email alerts
|

Mating quadratic maps with the modular group

Abstract: We prove that there exists a homeomorphism χ between the connectedness locus MΓ for the family Fa of (2 : 2) holomorphic correspondences introduced by Bullett and Penrose [BP], and the parabolic Mandelbrot set M1. We prove that the homeomorphism χ is dynamical (Fa is a mating between P SL(2, Z) and P χ(a)), that it is conformal on the interior of MΓ, and that it extends to a homeomorphism between pinched neighbourhoods of MΓ and M1 in the natural 1-parameter moduli spaces which contain them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(93 citation statements)
references
References 8 publications
(3 reference statements)
2
91
0
Order By: Relevance
“…In [3] it was observed that all quadratic maps with connected Julia sets could be realised in the family of correspondences (1). The advantage of the present analysis is that the surgery approach shows that matings of all quadratic polynomials having connected Julia sets with all faithful discrete representations of C 2 * C 3 having connected regular sets are realised in this family.…”
Section: Making the Correspondence Holomorphicmentioning
confidence: 72%
See 2 more Smart Citations
“…In [3] it was observed that all quadratic maps with connected Julia sets could be realised in the family of correspondences (1). The advantage of the present analysis is that the surgery approach shows that matings of all quadratic polynomials having connected Julia sets with all faithful discrete representations of C 2 * C 3 having connected regular sets are realised in this family.…”
Section: Making the Correspondence Holomorphicmentioning
confidence: 72%
“…This completes the proof of Theorem 1. Moreover since the projection (z, w) → z of S toĈ is a double cover with one double point, over the fixed point P of ρ, and two branch points, over T and the critical value of q, it follows by a calculation of Euler characteristic that S is of genus zero and hence, from the analysis in [3], that following a change in variable the relation p(z, w) = 0 can be put in the form…”
Section: Making the Correspondence Holomorphicmentioning
confidence: 99%
See 1 more Smart Citation
“…A one (complex) parameter family of holomorphic correspondences F a containing matings between the modular group and quadratic polynomials was discovered by the first author and Christopher Penrose nearly twenty years ago [4], and further investigated in [3] and [2]. Two naturally defined subsets of interest in the parameter space are:…”
Section: Introductionmentioning
confidence: 99%
“…This boundary should contain both the Julia set of the polynomial and the limit set of the group. The first examples of such matings are due to S. Bullett and C. Penrose [6], who mated representations of C 2 * C 3 in P SL(2, C) (in particular the modular group) with quadratic polynomials.…”
Section: Marianne Freibergermentioning
confidence: 99%